Iron‐catalyzed C(5)−H Imidation of Azole with N‐Fluorobenzenesulfonimide. Issue 24 (18th October 2017) - Wang, Xiaojiao; Lei, Bowen; Ma, Lifang; Jiao, Huixuan; Xing, Wenhua; Chen, Jiaming; Li, Ziyuan
Abstract: An iron(II)‐catalyzed direct imidation of oxazole and thiazole with N ‐fluorobenzenesulfonimide (NFSI) through C(5)−H bond cleavage is disclosed, providing C5‐imidated azoles in moderate to excellent yields with broad substrate scope. This reaction represents the first iron‐catalyzed C−H imidation of arene where NFSI serves as the imidation reagent, and potentially constitutes an efficient access to C5‐functionalized azole with great medicinal significance. Abstract :